215k views
5 votes
Find and simplify the expression if f(x)=x^2-10.

f(4+h)-f(4)=

User Petrux
by
5.2k points

2 Answers

7 votes


f(4+h)-f(4)=(4+h)^2-10-(4^2-10)\\f(4+h)-f(4)=16+8h+h^2-10-16+10\\f(4+h)-f(4)=h^2+8h

User Calidus
by
6.0k points
7 votes

Answer:


f (4 + h) -f (4) = h ^ 2 + 8h

Explanation:

We have the following quadratic function.


f (x) = x ^ 2-10

We must find the following expression


f (4 + h) -f (4) =

First we must find
f (4 + h)

Then substitute
x = (4 + h) in the quadratic equation:


f (4 + h) = (4 + h) ^ 2 -10\\\\f (4 + h) = 16 + 8h + h ^ 2 -10\\\\f (4 + h) = h ^ 2 + 8h +6

Now we find
f(4). Replace
x = 4 in the function
f (x)


f (4) = (4) ^ 2-10\\\\f (4) = 16-10\\\\f (4) = 6

Finally we have to:


f (4 + h) -f (4) = h ^ 2 + 8h +6 - 6


f (4 + h) -f (4) = h ^ 2 + 8h

User Dmitry Stropalov
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.